2016
DOI: 10.1164/rccm.201504-0733oc
|View full text |Cite
|
Sign up to set email alerts
|

Polyfunctional T-Cell Signatures to Predict Protection from Cytomegalovirus after Lung Transplantation

Abstract: Rationale: Cytomegalovirus (CMV), which is one of the most common infections after lung transplantation, is associated with chronic lung allograft dysfunction and worse post-transplantation survival. Current approaches for at-risk patients include a fixed duration of antiviral prophylaxis despite the associated cost and side effects.Objectives: We sought to identify a specific immunologic signature that predicted protection from subsequent CMV.Methods: CMV-seropositive lung transplantation recipients were incl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
68
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 78 publications
(71 citation statements)
references
References 33 publications
2
68
0
Order By: Relevance
“…This is in general consistent with previous observations, where CD4 T cells responding to viral peptides produced IFN γ and other cytokines and mobilized CD107a/b to surface . A polyfunctional response has been associated with efficient control of viral infections, including HCMV, HIV‐1, and hepatitis C , and might also be important in the response to HHV‐6B. In addition to confirming previous observations of degranulation , we found evidence of intracellular storage of granzyme B and observed antigen‐specific cytotoxic activity, both highlighting a direct effector role of CD4 T cells in the control of HHV‐6B, as previously suggested .…”
Section: Discussionsupporting
confidence: 92%
“…This is in general consistent with previous observations, where CD4 T cells responding to viral peptides produced IFN γ and other cytokines and mobilized CD107a/b to surface . A polyfunctional response has been associated with efficient control of viral infections, including HCMV, HIV‐1, and hepatitis C , and might also be important in the response to HHV‐6B. In addition to confirming previous observations of degranulation , we found evidence of intracellular storage of granzyme B and observed antigen‐specific cytotoxic activity, both highlighting a direct effector role of CD4 T cells in the control of HHV‐6B, as previously suggested .…”
Section: Discussionsupporting
confidence: 92%
“…This analysis clearly showed that CD8 + T-cell responses in healthy individuals were predominantly directed towards LTA and STA, while VP1, VP2 and VP3 antigens were comparably less frequently recognised ( Figure 1a). [12][13][14] To further expand the functional profiling of BKV T cells, we assessed polyfunctional capability of antigen-specific T cells from both healthy individuals and kidney transplant recipients. Extension of BKVspecific T-cell profiling to kidney transplant recipients revealed that patients with viral load of >1 10 3 copies per mL in plasma (referred to as high viraemic recipients) had significantly reduced CD8 + and CD4 + T-cell reactivity against STA and/or LTA antigens when compared to healthy individuals (Figure 1a and b).…”
Section: Kidney Transplant Patients With High Viraemia Show Altered Tmentioning
confidence: 99%
“…Previous studies have highlighted the importance of the polyfunctional profile of antigen-specific T cells and its impact on disease outcomes. [12][13][14] To further expand the functional profiling of BKV T cells, we assessed polyfunctional capability of antigen-specific T cells from both healthy individuals and kidney transplant recipients. In vitro expanded BKVspecific T cells were assessed for the production of IFN-c, TNF, CD107a and IL-2 by intracellular cytokine staining following stimulation with HLA class I-restricted BKV-specific T-cell epitopes (Figure 2a).…”
Section: Kidney Transplant Patients With High Viraemia Show Altered Tmentioning
confidence: 99%
“…Given that polyfunctional T cells confer a more effective immune response to infections (Yamamoto et al, 2009; Boyd et al, 2015; Snyder et al, 2016), it is important to investigate the impact of aging on T cell polyfunctionality. Van Epps et al demonstrated enhanced polyfunctionality in CD8 + T EM cell subsets in older individuals, but both CD4 + and CD8 + T CM cells exhibited an age-associated decline in polyfunctionality (Van Epps et al, 2014).…”
Section: The Aging Immune Systemmentioning
confidence: 99%